2016
DOI: 10.14744/nci.2016.72677
|View full text |Cite
|
Sign up to set email alerts
|

Acute gastric dilatation due to binge eating may be fatal

Abstract: Acute gastric dilatation was first described by Duplay in 1833. Since the stomach has rich blood circulation, necrosis and perforation due to dilatation are rarely seen. Clinically, more than 90% of cases have complaints of vomiting. The most useful method to determine diagnosis and etiology is computerized tomography (CT). Medical treatment is suitable for cases that have no necrosis or peritonitis findings. Delay in surgical treatment increases the risk of mortality. The present case is that of a diagnosis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…Some case reports reported fatal outcomes caused by the extreme acute gastric dilation after a binge episode [85][86][87][88]. It has been hypothesized that the massive food intake might cause an acute gastric dilatation, compressing the gastric wall and producing necrosis and perforation of the stomach [87]. Kim et al [89] reported a case of a 26-year-old woman who developed after a binge episode a huge gastric distension associated with acute pancreatitis.…”
Section: Binge Eating Disordersmentioning
confidence: 99%
“…Some case reports reported fatal outcomes caused by the extreme acute gastric dilation after a binge episode [85][86][87][88]. It has been hypothesized that the massive food intake might cause an acute gastric dilatation, compressing the gastric wall and producing necrosis and perforation of the stomach [87]. Kim et al [89] reported a case of a 26-year-old woman who developed after a binge episode a huge gastric distension associated with acute pancreatitis.…”
Section: Binge Eating Disordersmentioning
confidence: 99%
“…AGD without perforation can be managed conservatively in some cases [45,47]. However, with gastric perforation, definitive surgical management is necessary [36,45,47].…”
Section: Managementmentioning
confidence: 99%
“…Imaging studies such as abdominal or chest X-ray may reveal gas distension and subdiaphragmatic free air in cases with perforation [45,47]. Abdominal CT remains the most useful imaging modality for diagnosis and revealing of aetiology [10,47].…”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Anorexia nervosa confers a high degree of mortality and morbidity, including gastrointestinal disturbances [1][2][3]. While not fully understood, gastric distention can result from erratic eating behaviors, which may lead to decreased gastric motility and delayed gastric emptying [4].…”
Section: Introductionmentioning
confidence: 99%